(untitled) (NBPA Journal for Arts, Humanities & Social Sciences, 2025)
The objective of this paper is to show that the principal teaching of the Śrīmadbhagavadgītā is the teaching of love. This teaching of love has been rendered through all three yogas, i.e., karma yoga, jñāna yoga, and bhakti yoga. This teaching takes its birth in the womb of karma yoga, and subsequently it is nurtured by jñāna yoga and ultimately becomes mature at the hands of bhakti yoga. This love is unconditional and universal. The whole paper is an attempt to substantiate this view.